2011
DOI: 10.1016/j.powtec.2010.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of operating conditions and particle properties on performance of vertical air-lift

Abstract: The effect of the fluidization air flow rate and the transport air velocity on the solids mass flow rate and the pressure drop along the transport pipe was investigated in a vertical air-lift. The use of two different materials, glass (150 µm) and zirconium oxide (260 µm) particles (Geldart's B class), enabled to estimate the effect of particle properties on the air-lift performance. Different levels of the solids mass flow rate were obtained by varying the fluidization air flow rate while keeping the transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Some researchers proposed the model based on the balance of momentum by Kato et al., 5 Mahrous, 46 Yoon et al., 47 and Ma, 37 based on empirical correlation by Kawashima, 48 based on the power balance by Dedegil, 49 based on the multi-fluid model by Tomiyama et al., 50 and Hatta et al. 36 Other researchers, 51 such as Tomiyama et al., 51 Yoshinaga and Sato, 8 Hatta et al., 36 Hatta et al., 52 Liang and Peng, 53 Pougatch and Salcudean, 6 Cazarez et al., 54 Chladek et al., 34 and Hu et al. 4 conducted experimentally and analytically three-phase flow in vertical pipes.…”
Section: The Theoretical Studymentioning
confidence: 99%
“…Some researchers proposed the model based on the balance of momentum by Kato et al., 5 Mahrous, 46 Yoon et al., 47 and Ma, 37 based on empirical correlation by Kawashima, 48 based on the power balance by Dedegil, 49 based on the multi-fluid model by Tomiyama et al., 50 and Hatta et al. 36 Other researchers, 51 such as Tomiyama et al., 51 Yoshinaga and Sato, 8 Hatta et al., 36 Hatta et al., 52 Liang and Peng, 53 Pougatch and Salcudean, 6 Cazarez et al., 54 Chladek et al., 34 and Hu et al. 4 conducted experimentally and analytically three-phase flow in vertical pipes.…”
Section: The Theoretical Studymentioning
confidence: 99%
“…Thus, investigation on the conveying characteristics of a top-discharge blow tank will be favorable to industrial applications. Chladek et al [27] investigated a vertical air-lift which was similar to the top-discharge blow tank. Ratnayake et al [11] formulated a model to predict the entry pressure loss in a top-discharge blow tank, and the predicted values agreed well with the experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…Most research is focused on the discharge characteristics of bottom discharge blow tanks [13][14][15][16][17][18]. A few publications [19][20][21] on vertical pneumatic conveyers with a fluidized-bed solids feeder or vertical air-lift which was similar with top discharge blow tank in structure indicated that the solid mass flow was affected by the fluidizing and transporting gas flow rates, height of fluidized bed, riser diameter, and riser length. The characteristics in terms of gas-solids two-phase flow structures and the apparent behavior of particles and fluidparticle interactions are closely linked to operating conditions, particle properties, and blow tank configurations.…”
Section: Introductionmentioning
confidence: 99%